Exploratory Study of Rubber Seed Shell as Partial Coarse Aggregate Replacement in Concrete - Khairunisa, Muthusamy; Norhaiza, Nordin; G., Vesuvapateran; M., Ali; N. A., Mohd Annual; H., Harun; H., Ullap (Maxwell Scientific Organization, 2014)
Malaysia being a major rubber trees growing country has been generating a large amount of rubber seed shell which regarded as waste. At the same time, the growing construction industry which boosts the concrete production trade has results in higher consumption of natural coarse aggregate which open the door for depletion of this material in future. This study focuses on investigating the possibility of integrating crushed rubber seed shell as partial coarse aggregate replacement material in concrete making. Total of five mixes consisting various content of crushed rubber seed shell as partial coarse aggregate replacement ranging from 0, 5, 10, 15 and 20%, respectively were prepared in form of cubes. All the specimens were water cured before tested at 7 and 28 days. The workability test, compressive strength test and flexural strength test of the mixes was conducted in accordance to MS26 Part 1: Section 2, BSEN 12390 and ASTM 293-79 respectively. Generally, workability, compressive strength and flexural strength decrease with the increase in the crushed rubber seed shell replacement level. However, mix consisting around 10% of crushed rubber seed shell is suitable for the application in concrete work.